(untitled) (Journal of Global Arts Studies, 2025)
Background： As humanity’s understanding of the world continues to deepen, our position in the vast universe has become increasingly ambiguous. This concept of "ambiguity" has gradually permeated contemporary art and design, particularly standing out in the field of visual communication design. As a medium that blends information dissemination with artistic expression, visual communication design is undergoing a shift from explicit representation toward ambiguous and polysemous forms of expression. Objective： This study focuses on "ambiguous expression" in visual communication design, thoroughly investigating its practical application value and representational characteristics, with the aim of providing theoretical support and creative inspiration for contemporary designers. Methods: The study employs a combined methodology of literature analysis and case studies of representative design works. It examines ambiguous expression through multiple lenses—including form, methodology, emotional resonance, and aesthetic principles—to systematically delineate its core characteristics. Furthermore, the research explores practical application strategies through cultural element extraction, the interplay of tangible and intangible design elements, and gradient aesthetics. Results: The research demonstrates that ambiguous design can effectively enhance the inclusivity, openness, and artistic quality of visual communication, while possessing multidirectional interpretability and heightened emotional expressiveness. Its characteristics—including abstraction, polysemy, and symbolic transformation—significantly enrich the expressive repertoire of visual language. Conclusion: Ambiguous expression represents not merely an innovation in design language, but more significantly serves as a crucial driver propelling visual communication art toward humanization, avant-garde experimentation, and futuristic development. It expands the boundaries of design practice and opens new possibilities for the evolution of future visual language systems.